Reducing water entry impact loads on offshore marine structures by forced air entrapment - Guzel, Bulent; Korkmaz, Fatih C. (TAYLOR & FRANCIS LTD, 2020)
In this study, the effect of air cushioning due to air entrapment on the water entry of cylinders is examined experimentally and numerically. Air entrapment is forced via corrugations on a cylinder. Emphasis is given to the early stages of penetration effecting the total impact forces. Jet flows, pileups and free surface elevation profiles are characterised and compared with the ones obtained with a smooth cylinder. At low Froude numbers (Fr < 3), while the jet flow does not separate and climbs up on the solid surface of the smooth cylinder, the flow separation occurs and a cavity is formed during the water entry of the corrugated cylinder. The maximum impact force is a function of the wetted length which depends on the flow separation point. The numerical results showed good visual agreement with the experiments. The impacts under air cushioning and early flow separation effects produced 30% smaller impact pressures.
Keywords: Air entrapment; corrugation; slamming; impact force; cylinder; SIMULATION; CYLINDERS; SURFACE; Engineering